White-matter astrocytes, axonal energy metabolism, and axonal degeneration in multiple sclerosis - Cambron, Melissa (Nature Publishing Group, 2012)
In patients with multiple sclerosis (MS), a diffuse axonal degeneration occurring throughout the white matter of the central nervous system causes progressive neurologic disability. The underlying mechanism is unclear. This review describes a number of pathways by which dysfunctional astrocytes in MS might lead to axonal degeneration. White-matter astrocytes in MS show a reduced metabolism of adenosine triphosphate-generating phosphocreatine, which may impair the astrocytic sodium potassium pump and lead to a reduced sodium-dependent glutamate uptake. Astrocytes in MS white matter appear to be deficient in β(2) adrenergic receptors, which are involved in stimulating glycogenolysis and suppressing inducible nitric oxide synthase (NOS2). Glutamate toxicity, reduced astrocytic glycogenolysis leading to reduced lactate and glutamine production, and enhanced nitric oxide (NO) levels may all impair axonal mitochondrial metabolism, leading to axonal degeneration. In addition, glutamate-mediated oligodendrocyte damage and impaired myelination caused by a decreased production of N-acetylaspartate by axonal mitochondria might also contribute to axonal loss. White-matter astrocytes may be considered as a potential target for neuroprotective MS therapies.